Advancements in understanding the molecular and immune mechanisms of Bartonella pathogenicity - Jin, Xiaoxia; Gou, Yuze; Xin, Yuxian; Li, Jingwei; Sun, Jingrong; Li, Tingting; Feng, Jie (Frontiers in Microbiology, 2023)
Bartonellae are considered to be emerging opportunistic pathogens. The bacteria are transmitted by blood-sucking arthropods, and their hosts are a wide range of mammals including humans. After a protective barrier breach in mammals, Bartonella colonizes endothelial cells (ECs), enters the bloodstream, and infects erythrocytes. Current research primarily focuses on investigating the interaction between Bartonella and ECs and erythrocytes, with recent attention also paid to immune-related aspects. Various molecules related to Bartonella’s pathogenicity have been identified. The present review aims to provide a comprehensive overview of the newly described molecular and immune responses associated with Bartonella’s pathogenicity.